Zoanthids (Anthozoa, Hexacorallia) from the Great Barrier Reef and Torres Strait, Australia: systematics, evolution and a key to species - Burnett, W.; Benzie, J.; Beardmore, J.; Ryland, J. (Coral Reefs, 1997)
Zoanthid taxonomy is currently in a state of chaos, with many described species very few of which can be reliably identiÞed. As part of a genetically based, objective reappraisal of the number of northern Australian species, a total of 355 zoanthid specimens were collected from 19 localities in the Great Barrier Reef and Torres Strait during 1992Ð1994. Specimens, initially assigned to one of ten morphological or ecological forms, were subjected to allozyme electrophoretic analysis. Analysis of genetic data revealed only seven discrete (i.e., non-interbreeding) groups in the family Zoanthidae. These groups, which are delimited by Þxed gene di¤erences, are considered species under a biological species concept. Some species show considerable morphological variation and have broad environmental tolerances. We provide the Þrst key to Great Barrier Reef zoanthid species based on our results and observations. Species can be di¤erentiated in the Þeld on the basis of gross colony morphology, sand encrusting habit, polyp form and habitat. Genetic data are also used to generate a phylogenetic hypothesis of relationships among the Zoanthidae, which is compared to previous morphologically based systems. Division of the group on the basis of mesenterial arrangement appears justiÞed, but nematocyst data appear less valuable in phylogenetic studies of the group than has been suggested previously.